Effects of strategic leadership, organizational innovativeness and information technology capability on effective strategy implementation - Palladan, Ahmad Aliyu; Abdul Kadir, Kadzrina; Yen, Wan Chong (Institut Pengurusan Kualiti (IPQ), 2016)
The paper examined the role of strategic leadership, organizational innovativeness, information technology capability on strategy implementation in tertiary institutions situated at Kaduna state, Nigeria. One hundred and twenty-four (124) questionnaires were administered to Deans of colleges/faculties of the institutions located in the state.Out of the number, one hundred and eight (108) questionnaires were retrieved.PLS-SEM was used to analysed the data. The result shows a significant relationship between strategic leadership, organizational innovativeness, IT capability and effective strategy implementation. The study recommends radical move from the present style of administration in Nigerian tertiary institution to new form of leadership, which strategic leaders ought to champion.This radical move should be supported by innovation and full utilization of IT facilities available to the institutions.This is the best time, considering the dramatical change and the serious reform the sector is witnessing presently.